Combined Treatment of Adipose Derived-Mesenchymal Stem Cells and Pregabalin Is Superior to Monotherapy for the Treatment of Neuropathic Pain in Rats - Shimaa Mohammad Yousof; Doaa Attia ElSayed; Amani A. El-Baz; Hanaa S. Sallam; Faten Abbas (Hindawi Limited, 2021)
Aims. Neuropathic pain following nerve injury does not respond well to most available pharmacological remedies. We aimed to compare the outcome of the addition of adipose-derived mesenchymal stem cells (ADMSCs) to pregabalin for neuropathic pain treatment. Methods. Adult female albino rats (n=100) were randomized to receive traumatic sciatic nerve injury or sham. Animals were then randomized to ADMSC treatment with or without pregabalin. We conducted a battery of neurobehavioral and electrophysiological to assess neuropathic pain. Following sacrifice, we evaluated the histological changes and gene expression of brain-derived neurotrophic factor (BDNF) in the sciatic nerve. Serum and sciatic nerve tissue pro- and inflammatory cytokine levels were also assessed. Results. (1) All treatments significantly improved thermal withdrawal latency, sciatic nerve conduction velocity, and proinflammatory cytokine levels in injured animals, with no significant effect of the combined treatments compared to pregabalin monotherapy (p<0.05 each). (2) Combined treatment significantly improved medial gastrocnemius electromyographic amplitude and sciatic function index compared to pregabalin monotherapy (p<0.05 each). (3) Combined treatment significantly increased the BDNF expression, decreased anti-inflammatory cytokine (p<0.05 each), and restored the structural nerve damage, compared to pregabalin monotherapy. Conclusions. Combined treatment is associated with greater improvement of the sciatic nerve structure and function. Further studies are warranted to study the mechanism of action of the combined treatment to improve neuropathic pain.